Carbohydrate mouth rinse: an ergogenic aid able of optimizing the performance. DOI: 10.5007/1980-0037.2011v13n2p158 - Henrique Bortolotti; Leandro Ricardo Altimari; Marcelo Vitor-Costa; Edilson Serpeloni Cyrino (Universidade Federal de Santa Catarina, 2011)
Studies have shown that the mere presence of carbohydrate in the human mouth promotes the activation of some specific brain regions, with a positive i mpact on physical performance. Thus, the strategy of carbohydrate mouth rinse has been recently adopted with success in strenuous exercise (> 70% VO2max) lasting approximately 60 min. In this respect, the objective of this study was to discuss, based on literature data, the efficacy of this strategy to improve physical performance, as well as the possible mechanisms involved. The results produced, although still preliminary, are promising and led us to believe that carbohydrate mouth rinse is an interesting strategy, especially because of its easy application, low cost and good efficacy in improving physical performance during intense and prolonged physical exercise